Street intercept method: An innovative approach to recruiting young adult high-risk drinkers - Graham, Kathryn; Bernards, S.; Clapp, J.; Dumas, T.; Kelley-Baker, T.; Miller, P.; Wells, S. (Wiley-Blackwell Publishing Ltd., 2014)
Introduction and Aims: Many young adults are risky drinkers who are often missed by general population surveys. The aim of the present study was to assess factors affecting participation rates in a street intercept approach to recruiting young adult bar-goers for an online survey. Design and Methods: Two hundred eighty-seven young adults were approached as they entered the bar district of a medium-sized city on two consecutive weekend nights. Of these, 170 met eligibility requirements and were invited to complete a 2 min street survey for which they were paid $5 and given a gift card for $50 or $100 to be redeemed when they completed a follow-up online survey. Results: Sixty-one per cent of eligible persons (n = 104) participated in the street survey, with greater participation on the second night (74% vs. 50%). Sixty-eight per cent (n =  71) of those who participated in the street survey completed the online survey, with no differences in response by age or student status; however, men were significantly more likely to complete the online survey if they received the higher incentive, had consumed less alcohol and were recruited before midnight. The larger incentive was especially effective at increasing completion rates for men who had consumed a larger amount of alcohol. Discussion and Conclusions: Street intercept is an effective and efficient recruitment method that can measure both drinking and other experiences in the event and link these data to information collected in follow-up research. Unlike recruitment through convenience samples, response rates and response bias can also be assessed.